Resonance-enhanced multiphoton ionization (REMPI) spectroscopy of p-chlorofluorobenzene - Tuttle, William D.; Gardner, Adrian M.; Wright, Timothy G. (Elsevier, 2017)
The S1 ← S0 (A ~ 1B2 ← X~ 1A1) electronic transition of para-chlorofluorobenzene has been investigated using resonance-enhanced multiphoton ionization (REMPI) spectroscopy. Assignment of the vibrational structure has been achieved by comparison with corresponding spectra of related molecules, via quantum chemical calculations, and via shifts in bands between the spectra of the 35Cl and 37Cl isotopologues. In addition, we have also partially reassigned a previously-published spectrum of para-dichlorobenzene.